1972
DOI: 10.1192/bjp.121.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Phosphokinase Activity in Newly Admitted Psychiatric Patients

Abstract: Increased serum creatine phosphokinase (C.P.K.) levels have been shown in acutely psychotic patients on admission to hospital (Meltzer, 1968). Little is known about C.P.K. activity in non-psychotic (e.g. neurotic) patients admitted under similar conditions. Psychotic patients have not been compared with non-psychotic patients over a period of time following admission. Examination of a single serum sample for C.P.K. activity in non-psychotic patients at the time of admission has shown no abnormality (Meltzer et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Elevation of serum CPK has been found in about 50%°of acutely psychotic patients (Meltzer and Moline, 1970;Gosling et al, 1972;Schweid et al, 1972), though Harding (1974) could not confirm these findings; reports differ about whether LDH and/or SGOT are often concomitantly raised. Generally the CPK levels return to normal within a few days to weeks; increased CPK activity has been found in 7.80% of nonpsychotic patients (Meltzer et al, 1971).…”
Section: Discussionmentioning
confidence: 91%
“…Elevation of serum CPK has been found in about 50%°of acutely psychotic patients (Meltzer and Moline, 1970;Gosling et al, 1972;Schweid et al, 1972), though Harding (1974) could not confirm these findings; reports differ about whether LDH and/or SGOT are often concomitantly raised. Generally the CPK levels return to normal within a few days to weeks; increased CPK activity has been found in 7.80% of nonpsychotic patients (Meltzer et al, 1971).…”
Section: Discussionmentioning
confidence: 91%
“…One of the earliest and most robust findings in clinical reports of schizophrenia is the incidence of psychosis-associated creatine kinase-emia (PACK), which refers to a marked spike in serum creatine kinase levels at the onset of acute psychotic episodes (Coffey et al, 1970; Faulstich et al, 1984; Gosling et al, 1972; Hermesh et al, 2002; Meltzer 1968, 1973, 1976; Meltzer et al, 1969, 1970; Martin et al, 1972; Schweid et al, 1972). Studies have reported that approximately half of acutely psychotic schizophrenic patients exhibit muscle-type PACK, though interestingly normal creatine kinase activity is observed in patients experiencing chronic episodes of psychosis (Hermesh et al, 2002; Melkersson et al, 2006).…”
Section: Linking Creatine With Cognition and Emotionmentioning
confidence: 99%
“…Psychiatric research workers have been interested in CPK activity since Schiavone & Kaldor (1965) first observed higher levels of the enzyme in schizophrenic patients. Subsequent studies have detected elevated CPK levels in acutely psychotic patients with a variety of diagnoses (Bengzon et al 1966;Meltzer 1968Meltzer , 1970Meltzer et al 1969;Coffey et al 1970;Gosling et al 1972). Meltzer's group (1970) found no associations between CPK level and other factors such as medication, plasma cortisol levels, catecholamines, physical activity and weight loss.…”
Section: Introductionmentioning
confidence: 99%